Vector subscriptions and sharing mechanism for content-based publish/subscribe system - Tao YOU; Qi-man WU; Chuan-wen WANG; Dong ZHONG; Cheng-lie DU (Tongxin xuebao)
The concept of vector subscriptions to support subscription adaptations was introduced.Novel algorithms were proposed for updating vector subscriptions in classic matching tree structures,and was presented sharing algorithms for vector subscriptions.These algorithms effectively reduce the impact of subscription changes in matching tree structures.Compared to re-subscriptions method,the algorithms significantly reduce the reaction time to subscription updates and can sustain higher throughput in the presence of high update rates.